Combined ingestion of polystyrene microplastics and epoxiconazole increases health risk to mice: Based on their synergistic bioaccumulation in vivo. (August 2022) - Sun, Wei; Yan, Sen; Meng, Zhiyuan; Tian, Sinuo; Jia, Ming; Huang, Shiran; Wang, Yu; Zhou, Zhiqiang; Diao, Jinling; Zhu, Wentao
Graphical abstract: Highlights: EPO damaged gut barrier by targeting gut microbiota and led to massive PS invasion. PS interfered hepatic metabolic clearance of EPO. A synergistic effect existed in the bioaccumulation of PS and EPO in vivo. Combined ingestion of PS and EPO aggravated pathological and functional damage. Combined ingestion of PS and EPO aggravated oxidative stress and metabolic disorders. Abstract: Microplastic and pesticide are two common environmental pollutants whose adverse effects have been widely reported, but it is unclear whether they cause combined toxicity in mammals. In this study, polystyrene microplastics (5 µm, 0.012 or 0.120 mg/kg) or/and epoxiconazole (0.080 mg/kg) were administered orally to mice for 6 weeks, their toxicity to liver and kidney was assessed from changes in histopathology, tissue function, oxidative defense system and metabolic profile. In addition, mechanism of combined toxicity was explored in terms of bioaccumulation levels, intestinal barrier, gut microbiota. Results showed that combined ingestion of polystyrene (0.120 mg/kg) and epoxiconazole caused more severe tissue damage, dysfunction, oxidative stress, and metabolic disorders compared to single exposure sources. Interestingly, occurrence of combined toxicity was associated with their increased accumulation in tissues. In-depth exploration found that epoxiconazole caused intestinal barrier damage by targeting the gut microbiota, leading to massive invasion and accumulation of polystyrene, which in turn interfered with the metabolic clearance of epoxiconazole in liver. In all, findings highlighted that polystyrene and epoxiconazole could cause combined toxicity in mice through the synergistic effect of their bioaccumulation in vivo, which provided new reference for understanding the health risks of microplastics and pesticides and sheds light on the potential risk to humans of their combined ingestion.